MODERATING EFFECT OF TECHNOLOGY READINESS ON ADOPTION OF GEOTAGGING TECHNOLOGY AMONG SOCIAL NETWORKING SITES (SNSS) USERS FOR SMART TOURISM - Mohammad Badruzzaman BHUIYAN; Md. Aminul ISLAM; Md. Ziaul HAQUE; Chhanda BISWAS (Geo Journal of Tourism and Geosites, 2021)
More recently social networking sites (SNSs) users are extensively using the emerging geotagging technology for tourism motivation. The study aims to examine the relationship between determinants of geotagging technology and intention to adopt geotag technology as well as the extent to which technology readiness moderates the link between determinants of geotagging technology and intention to adopt geotag technology. Data were collected from a sample of 356 university students by using convenience sampling technique. Partial least square structural equation modelling has been used to measure the results. The empirical outcome uncovers that social influence, performance expectancy and facilitating condition are the factor that have direct impact on SNSs user’s willingness to adopt geotag for smart tourism experience. The present paper enriches UTAUT model by understanding the association between two variables namely effort expectancy and performance expectancy as well as the moderating role of the technology readiness. The findings of the study will assist to SNSs service providers by understanding the moderating role of technology readiness in the relationship between determinants of geotagging technology and intention to adopt geotag technology.